Women’s representations in advertisements: conceptual explorations / As representações das mulheres em propagandas: explorações conceptuais - Amanda Maria Bicudo de Souza (Revista de Estudos da Linguagem, 2020)
Abstract: Unlike traditional visions show, metaphors are present not only in literary language, but also in everyday, scientific and philosophical languages. It is through the metaphors that we conceptualize the world and understand the most abstract concepts that we have. Based on this premise, this study investigates the conceptual metaphors found in advertisements of women’s magazines, based on the theories: the theory of conceptual metaphor proposed by Lakoff and Johnson (2002), considerations of Kovecses (2002) about this theory and particular character of metaphors in advertisements, as proposed by Velasco-Sacristán (2010) and Ungerer (2003). The purposes of this research are to examine how the metaphors conceptualize the product advertised and how they reveal the social representation of women. The research was done through analysis of four advertisements taken from the magazines: Nova (Dec. 2008), Marie Claire (Oct. 2008), Cláudia (July 2009) and one advertisement taken from a website, published in 2020. The results show that conceptual metaphors are tools used by propagandists in the creation of advertisements based on stereotypes, representations and ideologies of particular group to which the advertisement is intended. Such resources tend to persuade the reader to purchase the product released.